Bolaamphiphiles based novel liposomes: a possible approach for drug delivery. (16th August 2010) - Vaidya, Bhuvaneshwar; Goyal, Amit K.; Khatri, Kapil; Mishra, Neeraj; Paliwal, Rishi; Rai, Shivani; Tiwari, Shailja; Vyas, Suresh
The present study was designed to develop a novel liposomal system containing dequalinium chloride (DEQ) as a charge-imparting constituent. Liposomes were prepared by cast film method with EPC:chol:DEQ molar ratio of 7:1:2. The novel liposomes were characterised for surface morphology, size and size distribution, entrapment efficiency and in vitro release study. Effect of osmotic shock was performed for establishment of liposomal bilayer stability and results demonstrated that incorporation of dequalinium chloride to the liposomal bilayer hindered the movement of entrapped solute. The hemolysis study was performed for estimation of its toxicological behaviour, if any. Cell-uptake studies showed that developed carrier could be useful for higher penetration in the cells compared to conventional liposomes. This being the first finding of its kind could open up a new era for the use of bolaamphiphiles like DEQ as an integral part of well established carrier like liposomes to provide them additional stability and efficacy.